2000
DOI: 10.1086/312623
|View full text |Cite
|
Sign up to set email alerts
|

Deeply Penetrating Banded Zonal Flows in the Solar Convection Zone

Abstract: Helioseismic observations have detected small temporal variations of the rotation rate below the solar surface that correspond to the so-called "torsional oscillations" known from Doppler measurements of the surface. These appear as bands of slower- and faster-than-average rotation moving equatorward. Here we establish, using complementary helioseismic observations over 4 yr from the GONG network and from the MDI instrument on board SOHO, that the banded flows are not merely a near-surface phenomenon: rather, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
172
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(199 citation statements)
references
References 20 publications
(21 reference statements)
24
172
3
Order By: Relevance
“…Recently, helioseismic techniques have been applied to probe the depth extent of torsional oscillations (e.g., Kosovichev & Schou 1997;Schou et al 1998). The flows have been seen to extend to depths of 56 Mm (Howe et al 2000). Furthermore, Beck & Schou (2000) have seen torsional oscillation patterns in supergranulation.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, helioseismic techniques have been applied to probe the depth extent of torsional oscillations (e.g., Kosovichev & Schou 1997;Schou et al 1998). The flows have been seen to extend to depths of 56 Mm (Howe et al 2000). Furthermore, Beck & Schou (2000) have seen torsional oscillation patterns in supergranulation.…”
Section: Introductionmentioning
confidence: 91%
“…Analysis of f-mode frequency splitting (Kosovichev & Schou 1997) has detected the existence of torsional oscillation at a depth of 2-9 Mm. More recently, it was found that this phenomenon extends to a depth of 0.92 R (Howe et al 2000), and might extend down to the tachocline through the entire convective zone (Vorontsov et al 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Solar rotation rates have been widely studied by use of direct Doppler velocity measurements (e.g., Howard & LaBonte 1980), by tracking photospheric magnetic or supergranular features (e.g., Meunier 1999), and by both global and local helioseismology (e.g., Thompson et al 1996;Giles 1999). The solar-cycle variations of solar rotation known as torsional oscillations were first observed by Howard & LaBonte (1980), and then studied by many researchers using different approaches (e.g., Snodgrass 1985;Howe et al 2000;Ulrich 2001). Torsional oscillation is a phenomenon of mixed faster and slower rotational bands relative to a smooth rotation profile in each hemisphere, with the faster rotational bands residing on the equatorial side of the solar activity belts.…”
Section: Introductionmentioning
confidence: 99%
“…To search for such variations, the data are analyzed in segments of a few months; the average over time of these results, as a function of (ro,0 0 ) is computed, and the residuals obtained by subtracting the average from the inferred rotation rate for each segment are investigated. In the outer parts of the convection zone the results show bands of slightly more rapid and slower rotation, often described as zonal flows, which converge towards the solar equator as time progresses, with an apparent Ll-year periodicity (e.g., Antia & Basu 2000;Howe et al 2000a;Vorontsov et al 2002). show that these variations extend through a substantial fraction of the convection zone.…”
Section: The Solar Internal Rotationmentioning
confidence: 87%